Exploring Counselor‐Client Agreement on Clients' Work Capacity in Established and Consultative Dyads. Issue 3 (11th September 2020) - Millner, Uma Chandrika; Brandt, Diane; Chan, Leighton; Jette, Alan; Marfeo, Elizabeth; Ni, Pengsheng; Rasch, Elizabeth; Rogers, E. Sally
Abstract : Counselor‐client agreement on the work capacity of clients living with serious mental illnesses informs the counseling relationship and facilitates accurate assessments of client eligibility for public programs. In this exploratory mixed‐methods study, we assessed counselor‐client agreement on clients' work capacity in 61 established therapeutic dyads and compared it with 30 dyads involved in an initial assessment session. Intraclass correlation coefficients and mountain plots were used to examine counselor‐client agreement. Results revealed moderate counselor‐client agreement of work capacity for both dyads. Counselor interviews illuminated sources of discordance. These results have practical implications for assessing the work capacity of clients.